Livestock credit in Nigeria: A case of the smallholder fattening scheme - Gefu, J.O. (International Livestock Centre for Africa, 1992)
Re-examines the stated success of the Smallholder Fattening Scheme, one of the sub-projects under the Second Livestock Development Project in Nigeria designed to improve the quality and weight of cattle at slaughter by establishing smallholder cattle fattening credit schemes in different parts of the country, in terms of loan recovery rate, liveweight gains achieved, and profit margins.